The Effect of Balance Exercise (Forward Stepping) on The Risk of Falling in the Elderly - Esri Rusminingsih; Marwanti Marwanti; Endang Sawitri; Apriliana Dwi Cahyani (Urecol Journal. Part C: Health Sciences, 2021)
Falling is a common occurrence in the elderly and the risk of falling increases with age. The elderly will experience a physical deterioration in the musculoskeletal system, which causes a decrease in balance, making them prone to falling. Impaired balance is the main cause of the risk of falls in the elderly because of visual, vestibular and somatosensory disorders. The risk of falling in the elderly can lead to complications of fractures and even death. Elderly balance exercise can be used as an effort to improve the quality of life of the elderly in the community. This study aims to determine the effect of balance training (forward stepping) on ??the level of risk of falling in the elderly. The research design used a pre-experiment with the One-Group Pretest-Posttest Design. The sampling technique used random sampling with a total of 16 respondents with criteria over 65 years of age, independent mobility and not experiencing hearing and vision problems. The intervention was given in the form of forward stepping balance exercises 3 times a week for 4 weeks with a duration of 15 minutes. Measuring the risk of falling using the Time Up and Go Test (TUGT). The results showed that the mean age of the elderly was 72.38 ± 3.46 years, with 12 more elderly women (75%) than men. The risk of falling before being given training in the elderly was included in the light category with an average TUGT value of 17.06 seconds and after training there was a decrease to an average of 13.24 seconds. The Wilcoxon Test shows the effect of balance training (forward stepping) on ??the risk of falling in the elderly with p-value = 0.000 <0.05. Conclusion: The results of this study indicate that balance training (forward stepping) can reduce the risk of falls in the elderly.